Silver nanoparticle-incorporated ultralong hydroxyapatite nanowires with internal reference as SERS substrate for trace environmental pollutant detection. (12th October 2018) - Zhang, Lei; Luo, Yongquan; Zhao, Yameng; Guan, Boxin; Zhang, Lingyi; Yu, Bohao; Zhang, Weibing
Abstract : Silver nanoparticle-incorporated HAPNWs as SERS substrates exhibit unique characteristics including stability, convenience and simple and environmentally friendly preparation. Abstract : Surface-enhanced Raman scattering (SERS) has wide applications because of its high sensitivity, convenience, rapid detection and numerous vibrational spectroscopic fingerprints. In this study, silver nanoparticle-incorporated ultralong hydroxyapatite nanowires (HAPNWs) as SERS substrates were used for highly sensitive SERS detection. HAPNWs were used to prepare AgNPs in situ using an aqueous solution containing AgNO3 under sunlight at room temperature without adding a reducing agent. The as-prepared highly flexible HAP nanowires were adopted for the fabrication of free-standing paper-like materials. The as-prepared ultralong HAP nanowires loaded with AgNPs not only possessed the merits of high flexibility and a porous network structure, but also exhibited unique characteristics of an SERS substrate including stability, convenience, and simple and environmentally friendly preparation. We discussed the fabrication, physical characterization and SERS activity of our SERS paper by measuring the Raman signals for a variety of model analytes. The SERS substrate was found to be highly sensitive and amiable to several different target analytes. The substrate also showed high stability and reproducibility. Subsequently, the potential practical application of the SERS paper was evaluated by quantitative analysis of an organic pollutant benzidine with an internal reference in environmental samples. Good linearity was demonstrated between 0.4 and 6.0 μM for benzidine with a correlation coefficient of 0.9919, and the limit of detection was 0.2 μM. The recovery ranged from 117% to 140% for benzidine in environmental water. These results indicated promising potential of the HAPNWs@AgNP paper as the SERS substrate for trace environmental pollutant detection.